PORE PRESSURE PREDICTION AND MODELING USING WELL-LOG DATA IN WEST BARAM DELTA, OFFSHORE SARAWAK BASIN, MALAYSIA - DEJEN , TEKLU ASFHA (2020)
Accurately predicted pore pressure is vital throughout the lifetime of any oil and gas field starting from exploration to the production stage. West Baram Delta (WBD), offshore Sarawak Basin, is characterized by variable depth of top overpressure zones. Hence, valid pore pressure prediction prior to drilling is critical to reduce drilling risks, increase the efficiency of reservoir modeling, and optimize costs. Moreover, the WBD is a mature field where enhanced oil recovery is of high interest and pore pressure evaluation is crucial.